The potential of restorative approaches in domestic violence cases to contribute to more victim-centred responses - based on the experiences of two field-based research programs - Hera Gabor; Szego Dora (Temida)
The article aims to discuss the opportunities for a restorative approach in domestic violence (DV) cases based on the results of two empirical research. After describing the victims’ perspective, we introduce the shortcomings of institutional frontline responses that hinder the effective prevention and fight against domestic violence. At the end of the paper, some local support initiatives for victims of DV are described. We examine the aspects of these initiatives that bring them close to the restorative approach - although they do not explicitly label themselves as restorative.